A Methodology to Estimation of Savings Potential at Thermoelectric Plants in Colombia Based on ISO 50001 Standard - Tabares, Juan J.; Valencia, Melissa; Chamorro, Jose E.; Vidal, Juan R.; Quispe, Enrique C.; Tibaquirá, Juan E. (International Journal of Energy Economics and Policy, 2023)
The ISO 50001:2018 standard establishes a standardized set of concepts and practices for energy management of industrial assets and processes, providing criteria to establish policies, processes, procedures, and tasks related to energy management to meet established energy objectives. This article presents the application of these tools in thermal power generation systems in Colombia to analyze their energy performance, study possible saving potentials and propose strategies to improve their energy efficiency. As a result, a savings potential of 18568.4 GWh and 2008.7 GWh in 15 years was found for operation, maintenance, and production planning, respectively.